O jornalismo público e a experiência na Diretoria de Comunicação do Tribunal de Justiça da Paraíba - Sousa Neto, Genésio Alves de (2016)
The research makes a relation of Public Journalism, in the mold of the movement started in the USA in the 1990s, with the experience of journalism received by the Communications Department of the Court of Justice of Paraíba, specifically, based on a study done in the project "Justice In Her Neighborhood - Woman Deserves Respect ", idealized to discuss with the communities guidelines on domestic violence against women, in the parameter of the Maria da Penha Law. It is a research of an exploratory nature, whose objective was to analyze the procedures adopted by the Board of Directors in the coverage of the project, in parallel to the traditional journalistic means. In the study we emphasize the relationship of Public Journalism with the experiences lived in our country, which in practice reveal a conception of what becomes Public Journalism. The crisis of journalism in the late twentieth century and the advent of the internet, a vector in the introduction of new media, have brought strong appeals in interactivity and in the spread of social networks. These transformations opened possibilities in the market, proximity and reflections in theories. They accelerated the day-to-day information and valued the sources. The research concluded that there are criteria of Public Journalism in the object of study, although they are self-localized, but they reveal a growing trend of professionalism of journalists working in the public sector and that these sectors need to be reorganized and structured to meet journalism expectations.